Identification of testis development-related genes by combining Iso-Seq and RNA-Seq in Zeugodacus tau - Liu, Peipei; Li, Ziniu; Zhang, Qiuyuan; Qiao, Jiao; Zheng, Chenjun; Zheng, Wenping; Zhang, Hongyu (Frontiers in Cell and Developmental Biology, 2024)
Zeugodacus tau (Walker) is an invasive pest. An effective method to control this pest is the sterile insect technique (SIT). To better apply this technique, it is necessary to understand testis development progression. In this study, we identified 292,33 transcripts from Z. tau testes by PacBio Iso-Seq, which provided an RNA expression profile during testis development. RNA-Seq library of Z. tau testes on day 1, 6, and 11 post eclosion were constructed. We identified 755 and 865 differentially expressed genes (DEGs) in the comparisons of T6 (testes on day 6) vs. T1 and T11 vs. T1, respectively. The KEGG pathway analysis showed that the DEGs were significantly enriched in retinol metabolism, vitamin B6 metabolism, and ascorbate and aldarate metabolism pathways. Knockdown of retinol dehydrogenase 12-like (rdh12-like), pyridoxal kinase (pdxk) and regucalcin (rgn), the representative gene in each of the above 3 pathways, reduced the hatching rate of Z. tau offspring. In addition, we identified 107 Drosophila spermatogenesis-related orthologous genes in Z. tau, of which innexin 2 (inx2) exhibited significantly up-regulated expression throughout testis development, and the knockdown of this gene reduced offspring hatching rate. Our data indicated that rdh12-like, pdxk, rgn, and inx2 genes were related to testis development, and they were conserved in tephritid species. The findings provide an insight into testis development and spermatogenesis in tephritid species.